2022
DOI: 10.1002/advs.202202022
|View full text |Cite
|
Sign up to set email alerts
|

Binary Blend All‐Polymer Solar Cells with a Record Efficiency of 17.41% Enabled by Programmed Fluorination Both on Donor and Acceptor Blocks

Abstract: Despite remarkable breakthrough made by virtue of “polymerized small‐molecule acceptor (PSMA)” strategy recently, the limited selection pool of high‐performance polymer acceptors and long‐standing challenge in morphology control impede their further developments. Herein, three PSMAs of PYDT‐2F, PYDT‐3F, and PYDT‐4F are developed by introducing different fluorine atoms on the end groups and/or bithiophene spacers to fine‐tune their optoelectronic properties for high‐performance PSMAs. The PSMAs exhibit narrow b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 60 publications
(95 reference statements)
0
40
0
Order By: Relevance
“…Another design strategy involves the halogenation on both the core and linker moieties. Peng et al demonstrated three Y-series-based polymer acceptors, PYDT-2F, PYDT-3F, and PYDT-4F, with varying numbers of fluorine atoms on the end groups and bithiophene linkers . With the increasing of the number of fluorine substituent, narrow optical band gap, down-shifted HOMO level, reduced surface energy, and enhanced miscibility with the fluorinated donor polymer PM6 could be achieved.…”
Section: Polymer Acceptors For the Binary Active Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Another design strategy involves the halogenation on both the core and linker moieties. Peng et al demonstrated three Y-series-based polymer acceptors, PYDT-2F, PYDT-3F, and PYDT-4F, with varying numbers of fluorine atoms on the end groups and bithiophene linkers . With the increasing of the number of fluorine substituent, narrow optical band gap, down-shifted HOMO level, reduced surface energy, and enhanced miscibility with the fluorinated donor polymer PM6 could be achieved.…”
Section: Polymer Acceptors For the Binary Active Layermentioning
confidence: 99%
“…Peng et al demonstrated three Yseries-based polymer acceptors, PYDT-2F, PYDT-3F, and PYDT-4F, with varying numbers of fluorine atoms on the end groups and bithiophene linkers. 83 With the increasing of the number of fluorine substituent, narrow optical band gap, down-shifted HOMO level, reduced surface energy, and enhanced miscibility with the fluorinated donor polymer PM6 could be achieved. Especially, all-PSC based on PM6:PYDT-3F exhibited a maximum PCE of 17.41% with a high FF of 77.01% owing to the deep HOMO level of PM6 and the favorable morphology of the blend film.To create advanced Y-series-based polymer acceptors with excellent power conversion efficiency values of binary and non-binary all-polymer solar cells, a simultaneous investigation must be conducted on the Y-series-based small-molecule acceptors and linkers.…”
mentioning
confidence: 99%
“…In view of this, all-polymer based systems have been paid large efforts to by the field, as their stability should be intrinsically higher than those with small molecules, and the efficiency of these types of solar cells has also reached a decent level of 16%. [12][13][14][15][16][17][18][19][20][21] At the same time, different from the binary all-polymer blend with polymer donor and polymer acceptor, the one-pot-synthesized block copolymer systems are also considered a rising star for pursing the balance of efficiency and stability. [22][23][24][25] Accordingly, the prospect of promoting the efficiency of block copolymer-based OSCs could be bright, as its units are chemically bonded together, which would be beneficial to resisting the morphology degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Though this gap has been successfully alleviated by the new concept of a polymerized small molecular acceptor (PSMA), specifically PCEs are now over 16% in multiple cases. [21][22][23][24][25][26][27][28][29] Nonetheless, the operational and mechanical stability difficulties come back again, due to PSMAs partially inheriting the properties of small molecules. [30][31][32][33] Since current PSMA-type materials are the most promising candidates for high-efficiency, more efforts in boosting device stability are required that rely not only on chemistry innovation, but also effective device fabrication methods.…”
Section: Introductionmentioning
confidence: 99%